MENERAPKAN PENDIDIKAN KARAKTER BERLANDASKAN BUDAYA LOKAL PADA SEKOLAH DASAR BESTARI UTAMI, GARUT - Susanti, Santi; Silvana Rachmawati, Tine (EDUTECH CONSULTANT, 2018)
Globalization requires individuals to have competitiveness to survive of change. Individuals also should not forget the moral sides that must be maintained especially for us as the East. Education is the right path to instill both. The application of a curriculum characterized early on, can help one to absorb well the material being taught. However, the provision of a characteristic curriculum is commonly done by schools located in urban areas, which are expensive and earmarked for the haves. This condition does not apply to one school in Garut, which provides quality education to its students, with an international education pattern but affordable and open-minded, intended for children who want to study at the school without looking at the socio-cultural and economic background of their parents. The problem is how the pattern is applied, what is the character education that is applied to the student? The research finds that the pattern of education at Sekolah Dasar Bestari Utami, Garut, applies the egalitarian principle: equality and togetherness to each students. Learning patterns which applied to students train cognitive, conative, and motoric skills and direct them to become an individual that has the character of discipline, responsible, smart, creative, respecting others, and respecting the culture and environment around